Penerapan Metode Analytical Hierarchy Process dalam Pemilihan Human Personality - Azhar, Zulfi; Putri, Wan Hafizah Ainun Syah; Mahfuz, Rizky Putri (Explorer, 2025)
To obtain personality criteria based on the work provided, several agencies usually set standard personalities that prospective workers must possess, with the aim that workers can work in fields that support their personalities. Likewise, the Siumbut-umbut Kisaran Village Office sets standard personalities that must be possessed by each employee so that the work carried out has optimal results. This study aims to determine the type of personality appropriate for work in the Siumbut-umbut Kisaran Village Office using the Analytical Hierarchy Process (AHP) method. Decision Support Systems (DSS) are applied to overcome problems in determining standard personalities for employees so that work results are optimal. This study found that the highest personality priority is Phlegmatic (K2), and the prioritized alternative is Eva Wulandari (At1).